2018
DOI: 10.1212/wnl.0000000000005476
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of preclinical Alzheimer disease

Abstract: ObjectiveTo determine the prevalence of preclinical Alzheimer disease (AD) according to current classification systems by examining CSF from a representative general population sample of 70-year-olds from Gothenburg, Sweden.MethodThe sample was derived from the population-based H70 Gothenburg Birth Cohort Studies in Gothenburg, Sweden. The participants (n = 322, age 70 years) underwent comprehensive neuropsychiatric, cognitive, and somatic examinations. CSF levels of β-amyloid (Aβ)42, Aβ40, total tau, and phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 39 publications
3
68
1
1
Order By: Relevance
“…Alzheimer's disease (AD), the most common cause of dementia [6], is characterized by the accumulation of amyloid β (Aβ) and hyper-phosphorylation of the Tau protein, with additional reduced acetylcholine levels and cerebral blood flow [2,7]. Furthermore, modifications in the blood-brain barrier (BBB), oxidative stress, mitochondrial impairment, neuroinflammation, and alterations in the insulin signaling have been observed in this condition [8].…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease (AD), the most common cause of dementia [6], is characterized by the accumulation of amyloid β (Aβ) and hyper-phosphorylation of the Tau protein, with additional reduced acetylcholine levels and cerebral blood flow [2,7]. Furthermore, modifications in the blood-brain barrier (BBB), oxidative stress, mitochondrial impairment, neuroinflammation, and alterations in the insulin signaling have been observed in this condition [8].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the “real world” transferability of interventions emerging as effective in restricted samples of asymptomatic individuals with positive biomarkers will hardly be sustainable for our healthcare systems. Pathological AD markers are very common (i.e., 46%) in representative samples of older people [ 21 ], and it has been estimated that about 46.7 million Americans had preclinical AD in 2017 [ 22 ]. So, how can we translate these procedures on such a large scale to identify candidates for future disease-modifying treatments?…”
Section: Resultsmentioning
confidence: 99%
“…MCI (6) and control (6) samples were collected from the Gothenburg H70 Birth Cohort Studies in Gothenburg, Sweden 14,36 . These samples were obtained from the Swedish Population Registry and included both persons living in private households and in residential care and approved by the Regional Ethical Review Board in Gothenburg.…”
Section: And Control Csfmentioning
confidence: 99%
“…CSF is continuously produced, recycled and freely exchanged with the interstitial fluid in the brain, making it an ideal reservoir of soluble aggregates that can be reflective of toxic species present in the brain tissue for that disease stage. It has been demonstrated that soluble Aβ is secreted into the CSF, making it an ideal biomarker candidate for AD 11,14,15 . Although the concentrations of Aβ oligomers and monomers have been measured in AD CSF, due to a lack of suitably sensitive methods, the specific detection and quantification of the heterogeneity in morphology of soluble Aβ aggregates present in CSF have not yet been determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation